Russian Clinical Research Market: Problems and Prospects - I. I. Tsarikov; S. V. Miheenko (Informaciâ i Innovacii)
The global market for clinical trials is directed at harmonizing international cooperation to address issues of universal provision of high quality and availability of medicines. Considering the ubiquitous nature of digitalization, at the present stage there are a number of barriers that impede the close international cooperation of social agents in the clinical research industry: the fragmentation of the rules and requirements of ethical and legal regulation, as well as significant disadvantages in the popularization of such research in the public mind. The Russian clinical trials sector is lagging behind in the development of digital volunteer/patient search services, that reduces the ability to conduct large valid clinical trials with human participation. The article presents data from a comparative analysis of popular digital volunteer/patient search services currently available on the global Internet for their compliance with the requirements of a consumer request, and also suggests options for their improvement. The result of the study was the identification of problem areas of the modern market for international clinical trials, as well as factors lagging behind the Russian sector due to the imbalance of the legislative framework and the low quality of domestic digital platforms for promoting and attracting volunteers